2011
DOI: 10.1590/s1415-43662011001000005
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos de solo sob produção orgânica influenciados pelo preparo e por plantas de cobertura

Abstract: Este trabalho objetivou determinar a influência das plantas de cobertura crotalária (Crotalaria juncea), guandu (Cajanus cajan (L.) Millsp), mucuna-preta (Mucuna aterrima), sorgo vassoura (Sorgum technicum) e pousio, nos atributos químicos de solo cultivado com feijão e milho orgânicos, sob semeadura direta (SD) e preparo convencional (PC). O trabalho foi conduzido em Santo Antônio de Goiás, GO, em Latossolo Vermelho distrófico, no delineamento de blocos ao acaso, com quatro repetições. Em novembro de 2003 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
8
0
10
Order By: Relevance
“…notillage velvet bean and crotalaria) over three study years. Cunha et al (2011a), studying the influence of different cover crops on soil chemical properties (e.g. crotalaria and pigeon pea), reported no significant differences either, in the soil OM contents (layers 0-0.10 and 0-0.20 m) in two study years.…”
Section: Chemical Propertiesmentioning
confidence: 91%
“…notillage velvet bean and crotalaria) over three study years. Cunha et al (2011a), studying the influence of different cover crops on soil chemical properties (e.g. crotalaria and pigeon pea), reported no significant differences either, in the soil OM contents (layers 0-0.10 and 0-0.20 m) in two study years.…”
Section: Chemical Propertiesmentioning
confidence: 91%
“…Cu content was within the adequate nutritional range for this crop (Oliveira et al, 2009), which was not observed in the first cycle. Fe leaf contents were lower in the second cycle (Table 8), which can be attributed to the insolubilization of this element at pH close to alkalinity and to the complexing power of the organic matter, which reduces the availability of P for plants (Cunha et al, 2011). B leaf contents were also reduced compared with the first cycle, which can be related to its low concentration in the sewage sludge applied to the soil.…”
Section: Resultsmentioning
confidence: 96%
“…Outros autores, também relataram que as plantas de cobertura em geral não alteram o pH do solo (PAVAN et al 1986, CUNHA et al 2011, SOUZA 2012. Entretanto, na fase inicial do atual estudo, ZALAMENA (2012) observou aumento de pH nas camadas até 10 cm de profundidade do solo sob cultivo de plantas anuais (sucessão moha + azevém e trigo mourisco + aveia branca) em relação à testemunha.…”
Section: Resultsunclassified